The moderating impact of the organizational factors on the relationship between corporate governance and SEMs performance - Aldboush, Hassan; Abbadi, Sinan S.; Al-Abbadi, Lina Hamdan; Almasria, Nashat Ali (International Journal of Innovative Research and Scientific Studies, 2025)
The study aims to examine the mediating roles of organizational performance, culture, and support on the relationship between corporate governance and Small and Medium Enterprises (SMEs) performance in Oman. A quantitative method of research was used, and data were collected from 150 SMEs and later used to examine the effect of these factors on corporate governance and performance. Based on the study results, corporate governance correlates significantly with organizational performance, with organizational support culture serving as the mediating factors between corporate governance and organizational performance. Interestingly, organizational culture was a significant predictor of all the predictors. Such findings offer significant implications for both policymakers and business managers on how suitable frameworks for SMEs might be set in place. Therefore, future research studies ought to undertake cross-country analysis and the inclusion of other control variables to enhance the understanding of such relations in Oman.